Phenomenology of Bureaucracy Amidst the Chaos of State Civil Apparatus in the Papua Conflict Region - Elazhari Elazhari; M. Ikrar Budijaya (Universitas Medan Area, 2026)
This study aims to understand the adaptation strategies of State Civil Apparatus (ASN) in carrying out bureaucratic functions in conflict areas. This study used a qualitative approach with an interpretive phenomenological method. Informants were selected purposively, consisting of six ASN: three district employees, two civil servant teachers, and one health worker. Data were collected through in-depth interviews, contextual observation, and documentation. Analysis was conducted through rereading, thematic tagging, and hermeneutic interpretation. The results of the study: (1) physical and spatial adaptation, namely the transfer of services from offices to residents' homes or security posts; (2) relational adaptation, through negotiations with traditional leaders and armed groups; (3) psychological and spiritual adaptation, in the form of communal prayer, collective humor, and emotional solidarity; and (4) moral adaptation based on service motivation, where ASN persist not because of formal orders, but because of a sense of responsibility to the community. These findings strengthen the relevance of the theories of street-level bureaucracy (Lipsky), adaptive governance (Folke), public service motivation (Perry & Wise), and coping strategies (Lazarus & Folkman).